Marked Global DNA Hypomethylation Is Associated with Constitutive PD-L1 Expression in Melanoma - Chatterjee, Aniruddha; Rodger, Euan J.; Ahn, Antonio; Stockwell, Peter A.; Parry, Matthew; Motwani, Jyoti; Gallagher, Stuart J.; Shklovskaya, Elena; Tiffen, Jessamy; Eccles, Michael R.; Hersey, Peter (iScience, 2018)
Constitutive expression of the immune checkpoint, PD-L1, inhibits anti-tumor immune responses in cancer, although the factors involved in PD-L1 regulation are poorly understood. Here we show that loss of global DNA methylation, particularly in intergenic regions and repeat elements, is associated with constitutive (PD-L1CON), versus inducible (PD-L1IND), PD-L1 expression in melanoma cell lines. We further show this is accompanied by transcriptomic up-regulation. De novo epigenetic regulators (e.g., DNMT3A) are strongly correlated with PD-L1 expression and methylome status. Accordingly, decitabine-mediated inhibition of global methylation in melanoma cells leads to increased PD-L1 expression. Moreover, viral mimicry and immune response genes are highly expressed in lymphocyte-negative plus PD-L1-positive melanomas, versus PD-L1-negative melanomas in The Cancer Genome Atlas (TCGA). In summary, using integrated genomic analysis we identified that global DNA methylation influences PD-L1 expression in melanoma, and hence melanoma's ability to evade anti-tumor immune responses. These results have implications for combining epigenetic therapy with immunotherapy. [Display omitted] •Global DNA hypomethylation in melanoma promotes constitutive PD-L1 expression•Transcriptomic up-regulation accompanies constitutive PD-L1 expression in melanoma•Constitutive PD-L1 is associated with reduced DNMT3A expression and viral mimicry•DNA methylation inhibitor treatment of melanoma cells increases PD-L1 expression Genetics; Genomics; Cancer; Transcriptomics